Pengaruh Berbagai Metode Ekstraksi dari Ekstrak Etanol Umbi Bawang Tiwai (Eleutherine americana Merr) terhadap Rendemen Ekstrak dan Profil Kromatografi Lapis Tipis - Ayida Mawarda; Erwin Samsul; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
The bulb of Eleutherine americana Merr is a typical Kalimantan plant that has many medicinal properties. Many studies have been carried out with various extraction methods used to determine the compounds contained in the bulb of Eleutherine americana Merr. This study aims to determine the effect of the method and the extraction time on the yield value and thin layer chromatography profile (TLC) of the bulb of Eleutherine americana Merr extract. The extraction method uses 96% ethanol solvent using the maceration method for 2 weeks and ultrasonic bath method with time variables of 10, 20 and 30 minutes. The yield of maceration extract was 12% and the ultrasonic bath method was 12.5%, 17.5%, and 15% (10, 20, 30 minutes). In the TLC test there were no differences in the spot patterns of the two extraction methods. So it can be concluded that the extraction method affects the yield of extract but does not affect the extract compound content seen from the TLC spot pattern.